Influence of dietary methionine on body weight gain and composition in high-lean growth gilts fed from 100 to 240 lb - Friesen, K.G.; Owen, K.Q.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred-fourteen high-lean growth gilts (initial wt of 100 lb) were used to determine the level of digestible methionine required to optimize growth performance and carcass characteristics from 100 to 240 lb. The experiment was designed as a randomized complete block with blocks based on initial BW. Three pigs per pen and six pens per treatment were used. Gilts were fed a corn and soybean meal-based diet containing .21, .24, .27, .30, .33, or .36% digestible methionine (.25 to .425% total methionine) in both the grower and finisher periods. The grower diet (fed from 100 to 165 lb) was formulated to contain 1.17% total lysine (.94% digestible) and .52% cystine, whereas the finisher diet contained 1.01% total lysine (.83% digestible) and .49% cystine. Cornstarch was replaced by DL-methionine to provide the experimental methionine concentrations. Average daily gain, ADFI, and feed efficiency (F/G) were not influenced by increasing digestible methionine from 100 to 165 lb, 165 to 240 lb, or 100 to 240 lb. Neither average backfat thickness nor longissimus muscle area was influenced by increasing digestible methionine at 240 lb. From 100 to 240 lb, carcass protein and lipid accretion were not influenced by digestible methionine. The data from this experiment suggest that the methionine requirement for high-lean growth gilts is not greater than .25% total methionine (.21 % digestible methionine; 6 gld total methionine intake) from 100 to 240 lb. Thus, the required methionine: lysine ratios do not exceed 22 and 25% for high-lean growth gilts fed diets containing adequate cystine from 100 to 165 and 165 to 240 lb, respectively.
Keywords: Swine; Pigs; Methionine; Sulfur amino acids; Genotype; Carcass composition